Recent Contributions to the Study of the Reception of the Bible and Their Implications for Biblical Studies in Africa - Stenschke, Christoph (2015)
This article surveys a number of recent studies on the reception of biblical material in the Bible itself or in later works and periods. It endeavours to present studies that are representative of the nature and extent of the shift in the past two decades from the Bible itself to its rich reception history. An introductory section describes how recent developments in hermeneutics have shown to what extent hermeneutics is a historical discipline. After a detailed presentation and assessment, a final section draws some conclusion for the tasks ahead for biblical studies and related disciplines in Africa.
Keywords: reception of the Bible -- hermeneutics -- reading the Bible in Africa -- Africa -- Bible -- African Hermeneutics; Literaturbericht -- 2009-2014; Rezension